Non-UN Sanctions and the ‘Responsibility to Protect’: Legality, Legitimacy and their Significance for R2P - Stojkovski, Ljupcho (University of Ljubljana, Faculty of Law, 2023)
The Russian aggression on Ukraine has been accompanied by two things – the ineffectiveness of the UN Security Council regarding this war, and the enormous amount of non-UN sanctions against Russia for its violation of international law. When it comes to the Responsibility to protect (R2P), sanctions are part of its third Pillar since “collective action” in the name of R2P is a broad term that is not limited only to military intervention but can include other measures with or without the use of force. Under the accepted R2P version of 2005, however, collective action should be undertaken by the UN Security Council only. What remains unanswered is what should the international community’s response be under Pillar 3 in cases when the UN Security Council is ineffective because it is passive or blocked, and especially when one of the perpetrators of R2P crime(s) is a permanent member of the Council, like there are indications today, for example, with Russia’s war on Ukraine or with China’s treatment of its Uyghur population. If the use of force is not an option in these situations because of prudent reasons, are sanctions adopted outside of the UN (Security Council) warranted and sufficient under the R2P norm? What does the answer to this question, in turn, say about R2P’s potential (especially regarding Pillar 3) as a norm? The paper will deal with the present questions and will argue that non-UN sanctions are a legitimate R2P response that should be undertaken by the international community on a case-by-case basis when the Security Council is unable or unwilling to fulfill its responsibility. On the other hand, there is no easy answer when it comes to the sanctions’ sufficiency and their effects on R2P, and these aspects will depend and should be assessed in accordance with numerous situational factors.
Keywords: UN Security Council; UN Security Council (UNSC); Responsibility to Protect (R2P, RToP); Responsibility to Protect; Sanctions